Endoscopic Ultrasound-Guided Fine Needle Biopsy Needles Provide Higher Diagnostic Yield Compared to Endoscopic Ultrasound-Guided Fine Needle Aspiration Needles When Sampling Solid Pancreatic Lesions: A Meta-Analysis - Renelus, Benjamin D. (Clin Endosc, 2021)
BACKGROUND/AIMS: Studies comparing the utility of endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) and endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) for solid pancreatic lesions have been inconclusive with no clear superiority. The aim of this meta-analysis was to compare the diagnostic accuracy and safety between the two sampling techniques. METHODS: We performed a systematic search of randomized controlled trials published between 2012 and 2019. The primary outcome was overall diagnostic accuracy. Secondary outcomes included adverse event rates, cytopathologic and histopathologic accuracy, and the mean number of passes required to obtain adequate tissue between FNA and FNB needles. Fixed and random effect models with pooled estimates of target outcomes were developed. RESULTS: Eleven studies involving 1,365 participants were included for analysis. When compared to FNB, FNA had a significant reduction in diagnostic accuracy (81% and 87%, p=0.005). In addition, FNA provided reduced cytopathologic accuracy (82% and 89%, p=0.04) and an increased number of mean passes required compared to FNB (2.3 and 1.6, respectively, p<0.0001). There was no difference in adverse event rate between FNA and FNB needles (1.8% and 2.3% respectively, p=0.64). CONCLUSIONS: FNB provides superior diagnostic accuracy without compromising safety when compared to FNA. FNB should be readily considered by endosonographers when evaluating solid pancreatic masses.